Study of caffeine urine and saliva of horses subjected to urinary acidification - Carregaro, A. B.; Mataqueiro, M. I.; Soares, OAB; Queiroz-Neto, A. (Wiley-Blackwell, 2004)
The study of caffeine in racing horses has been of growing concern in veterinary sports medicine since the Association of Racing Commissioners International (ARCI) stated that it has no valid therapeutic use in racehorses. We examined the kinetic alterations in the urinary excretion and salivary secretion of caffeine in seven horses subjected to urinary acidification using ascorbic acid because this procedure can simulate the acidosis that follows anaerobic exercise. They participated in two treatment groups: the control group (SG) received 500 ml of saline and then 2.0 mg kg(-1) caffeine i.v. 30 min later; and the acidified group (AG) was subjected to urinary acidification with ascorbic acid at a dose of 0.5 g kg(-1) i.v. and then 2.0. mg kg(-1) caffeine i.v. 30 min later. Samples were collected 30 min before caffeine administration, immediately before caffeine administration (time zero) and at 0.25, 0.5, 1, 2, 4, 6, 8, 12, 24, 48 and 72 h afterwards. The samples were assayed by gas chromatography. The mean urinary pH for SG was 8.2, but for AG it was as low as 5.9 at 4 h, extending acidosis for up to 8 h. The kinetic curves for the two groups were similar for urinary excretion and salivary secretion. Differences occurred only in peak excretion and peak secretion in SG obtained at 1 h and 30 min, respectively, and in AG at 2 h and 1 h, respectively. This could be explained, in part, to the diuresis in AG compared with SG, resulting in less concentrated urine in the former group. The large difference between the pK(a) of caffeine and the pH of the medium may be responsible for the similar pharmacokinetics observed for the two groups. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: Horse; caffeine; urine; saliva; ascorbic acid; urinary acidification